BIBLIOMETRIC ANALYSIS OF CONSUMER BEHAVIOR OF LUXURY BRANDS - Anak Agung Ayu Prasasti Ayundari; Noer, Lissa Rosdiana (JURNAL MANAJEMEN MOTIVASI, 2026)
Public interest in purchasing "luxury brands" or luxury goods has recently increased. This study aims to analyze and evaluate publications related to luxury consumer behavior using systematic review and bibliometric analysis. 176 data from the Scopus database were used in this study. The results of this study show the dynamic development of studies related to luxury consumer behavior and the interesting research themes discussed related to this topic.